Improving Learning Achievement Through Jigsaw Type Cooperative Learning Model By Considering The Level of Misconception and Learning Motivation - Riadhatul Ulum; Muhammad Fath Azzajjad; Dewi Satria Ahmar (PT Mattawang Mediatama Solution, 2023)
This study aims to improve learning achievement through a jigsaw cooperative learning model by paying attention to the level of misconceptions and learning motivation on learning achievement in the Indonesian language subject at SDN Seruni 01, Jember Regency. Jigsaw is a multifunctional structure of cooperative learning structures. The research subjects were grade II students at Seruni 01 Public Elementary School in the eighth semester of the 2022/2023 academic year. The research subject is success in learning Indonesian. Methods of data collection is done through tests. The data analysis method used is descriptive analysis. The success criterion is a minimum class average according to the KKM score and a minimum classical advantage of 65%. In the first period, the willingness to learn increased from 56 percent to 83 percent in the second period. Data from Cycle II shows that the expected success achieved even exceeds the proposed learning success indicator. From this, the researcher concluded that Jigsaw cooperative learning applied in the learning process can improve learning.